Utilization of eggshell as a low-cost precursor for synthesizing calcium niobate ceramic. Issue 3 (16th August 2018) - Kamkum, Phonphan; Vittayakorn, Wanwilai; Seeharaj, Panpailin; Woramongkolchai, Somsak; Muanghlua, Rangson; Vittayakorn, Naratip
Abstract : This study investigated the possibility of using calcium carbonate (CaCO3 ) from chicken eggshell biowaste as a starting material for synthesizing calcium niobate (CaNb2 O6 ) powder through the conventional solid-state reaction. Phase formation of calcium niobate was studied as a function of calcination conditions by X-ray diffraction (XRD), Fourier transform infrared spectroscopy and Raman spectroscopy. The X-ray fluorescence results showed that the chicken eggshell contained more than 96·0% of calcium carbonate by weight. The structural characteristics of the calcium carbonate and calcium niobate powder were quantitatively evaluated by Rietveld refinement method from the XRD data. Rietveld refinement results verified that the eggshell powder exhibited a rhombohedral calcite (calcium carbonate) structure with lattice parameters a = b = 4·9812 ± 0·00059 Å (1Å = 0·1 nm) and c = 17·0342 ± 0·00292 Å with α = γ = 90° and β = 120°. Furthermore, the single phase of calcium niobate corresponded to the orthorhombic structure for space group Pbcn (60) obtained after the calcination process. The non-isothermal kinetic of calcium niobate was investigated by the Ozawa methods. Activated energy calculated using Ozawa methods was 1168 ± 29 kJ mol −1 . Also, there was no significant difference in dielectric properties between calcium niobate ceramic using chicken eggshell waste as a starting material and calcium niobate ceramic using analytical-reagent-grade calcium carbonate. This study showed that calcium carbonate from chicken eggshell biowaste is an alternative starting material for synthesizing microwave dielectric calcium niobate ceramic.